(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Antibiotic-associated diarrhea (AAD) develops through the loss of normal bacterial intestinal flora. We have conducted a case-control study in order to assess whether prophylactic administration of Saccharomyces boulardii (S. boulardii) prevents occurrence of AAD among adult hospitalized patients. Methods. Single-center hospital based case-control study was conducted in University Clinic “Dr Dragisa Misovic-Dedinje”, Belgrade, Serbia. Hospital records were screened in order to identify all the patients developing AAD in period January 1. 2010 – August 31. 2015. For every case, one age and gender matched control was randomly selected among patients hospitalized at the same time at the same department who were administered with antibiotics and did not develop AAD. For both cases and controls data were extracted on demographics, medical history, indication for use of antibiotics, antibiotics used, and prophylactic use of S.boulardii probiotics. The relationship between occurrence of AAD and putative risk factors were measured using the odds ratios (ORs) and their 95% confidence interval (CI) derived from logistic regression analysis. Results. Number of 59 cases and 59 controls were included in the study. Most of AAD cases were associated with old age (mean age of 78.05), and almost half (49.15%) were hospitalized on geriatrics department. Most prescribed class of antibiotics among cases was III generation cephalosporins (50.85%), followed by fluoroquinolones (28.81%) and trimethoprim-sulfamethoxazole (20.34%). Significantly more cases than controls were treated with carbapenems (16.95% vs. 5.08% respectively, p=0.04). Significantly less cases were administered with prophylactic S. boulardii probiotics (18.64% vs. 42.37% p=0.005). We identified prophylactic use of S. boulardii to act protectively against development of AAD from both univariate (OR: 0.31, 95% CI: 0.14-0.72) and multivariate analysis (OR:0.36, 95% CI: 0.14-0.80). Use of carbapenems was borderline significant risk factor for development of AAD in univariate (OR: 3.81, 95% CI: 0.99-14.64) as well as multivariate analysis (OR: 3.82, 0.91-16.08) (Table 3). Conclusion. Prophylactic use of probiotics containing Saccharomyces boulardii acts protectively against antibiotic-associated diarrhea among hospitalized patients.